2009
DOI: 10.1002/hyp.7370
|View full text |Cite
|
Sign up to set email alerts
|

Trend detection in hydrological series: when series are negatively correlated

Abstract: Abstract:The objective of this paper is to verify the applicability of the trend-free pre-whitening (TFPW) approach, developed by Yue et al. (2002) for positively correlated series, to negatively correlated series using similar Monte Carlo simulations. This study was initiated when a project on trend detection for streamflow and baseflow series across Canada revealed that a significant number of series had negative correlation coefficients. The TFPW procedure confirmed to be also well suited for negatively cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 4 publications
(20 reference statements)
0
17
0
Order By: Relevance
“…However, the MK statistic is highly sensitive to the serial dependence of a time series (Yue and Wang, 2002;Yue et al, , 2003. For instance, the variance of MK statistic S increases (decreases) with the magnitude of significant positive (negative) autocorrelation of a time series, which leads to an overestimation (underestimation) of the trend detection probability (Douglas et al, 2000;Wu et al, 2008;Rivard and Vigneault, 2009). To eliminate such affect, Von and Kulkarni and von Storch (1995) proposed a pre-whitening procedure that removes the lag-1 autocorrelation prior to applying the MK test, as employed by Río et al (2013) amid the above-cited studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the MK statistic is highly sensitive to the serial dependence of a time series (Yue and Wang, 2002;Yue et al, , 2003. For instance, the variance of MK statistic S increases (decreases) with the magnitude of significant positive (negative) autocorrelation of a time series, which leads to an overestimation (underestimation) of the trend detection probability (Douglas et al, 2000;Wu et al, 2008;Rivard and Vigneault, 2009). To eliminate such affect, Von and Kulkarni and von Storch (1995) proposed a pre-whitening procedure that removes the lag-1 autocorrelation prior to applying the MK test, as employed by Río et al (2013) amid the above-cited studies.…”
Section: Introductionmentioning
confidence: 99%
“…To eliminate such affect, Von and Kulkarni and von Storch (1995) proposed a pre-whitening procedure that removes the lag-1 autocorrelation prior to applying the MK test, as employed by Río et al (2013) amid the above-cited studies. However, such a procedure is particularly inefficient when a time series either features a trend or is serially dependent negatively (Rivard and Vigneault, 2009). In fact, the presence of a trend can lead to false detection of significant positive (negative) autocorrelation in a time series (Rivard and Vigneault, 2009), and removing this through a pre-whitening may remove (inflate) the portion of a trend, leading to the underestimation (overestimation) of trend detection probability and trend magnitude (Yue and Wang, 2002;Yue et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic idea of this approach is to preserve the true slope of linear trends by removing trend components prior to PW before recombining trend components and trend-free pre-whitened series. Rivard and Vigneault [22] and Blain [23] suggested that TFPW is suitable for trend detection in negative and positive serially dependent data if slopes of trends are estimated properly. However, recent studies provided empirical and theoretical proof that the TFPW is unsuitable to preserve the correct Type I error, which is the only indicator that can be controlled to prevent a false identification of numerous spurious trends.…”
Section: Introductionmentioning
confidence: 99%
“…Observed climatic series usually have short lengths and good correlations, so the MK results would be inaccurate and must be viewed with caution. To overcome the defects of the MK test, various approaches were suggested to remove the affects of serial correlation, such as pre-whitening, trend-free pre-whitening, variance correction and block resampling techniques [21][22][23].…”
Section: Introductionmentioning
confidence: 99%